Influence of mast cells in drug-induced gingival overgrowth - Subramani, Tamilselvan; Rathnavelu, Vidhya; Yeap, Swee Keong; Mohammed Alitheen, Noorjahan Banu (Hindawi Publishing Corporation, 2013)
Mast cells (MCs) are multifunctional effector cells that were originally thought to be involved in allergic disorders. Now it is known that they contain an array of mediators with a multitude of effects on many other cells. MCs have become a recent concern in drug-induced gingival overgrowth (DIGO), an unwanted outcome of systemic medication. Most of the studies have confirmed the significant presence of inflammation as a prerequisite for the overgrowth to occur. The inflammatory changes within the gingival tissue appear to influence the interaction between the inducing drug and the fibroblast activity. The development of antibodies to MC-specific enzymes, tryptase and chymase, has facilitated the study of mast cells in DIGO. Many immunohistochemical studies involving MCs have been conducted; as a result, DIGO tissues are found to have increased the number of MCs in the gingiva, especially in the area of fibrosis. At the cellular level, gingival fibrogenesis is initiated by several mediators which induce the recruitment of a large number of inflammatory cells, including MCs. The purpose of this paper is to access the roles played by MCs in gingival overgrowth to hypothesize a relationship between these highly specialized cells in the pathogenesis of DIGO.